A panchromatic analysis of starburst galaxy M82: probing the dust properties. Issue 1 (8th March 2014) - Hutton, Susan; Ferreras, Ignacio; Wu, Kinwah; Kuin, Paul; Breeveld, Alice; Yershov, Vladimir; Cropper, Mark; Page, Mat
Abstract: We combine near-ultraviolet (NUV), optical and IR imaging of the nearby starburst galaxy M82 to explore the properties of the dust both in the interstellar medium of the galaxy and the dust entrained in the superwind. The three NUV filters of Swift -Ultraviolet/Optical Telescope enable us to probe in detail the properties of the extinction curve in the region around the 2175 Å bump. The NUV colour–colour diagram strongly rules out a 'bump-less' Calzetti-type law, which can either reflect intrinsic changes in the dust properties or in the star formation history compared to starbursts well represented by such an attenuation law. We emphasize that it is mainly in the NUV region where a standard Milky Way-type law is preferred over the Calzetti law. The age and dust distribution of the stellar populations is consistent with the scenario of an encounter with M81 in the recent ≲400 Myr. The radial variation of NUV/optical/IR photometry in the galaxy region – including the polycyclic-aromatic-hydrocarbon-dominated emission at 8 μm – confirms the central location of the star formation. The radial gradients of the NUV and optical colours in the superwind region supports the hypothesis that the emission in the wind cone is driven by scattering from dust grains entrained in the ejecta. The observed wavelength dependence, ∝λ −1.5, reveals either a grain size distribution n ( a ) ∝ a −2.5, or a flatter distribution with a maximum size cutoff, suggesting that only small grains are entrained in the supernova-driven wind.